The politeness comments on the Indonesian president Jokowi instagram official account viewed from politico pragmatics and the character education orientation in the disruption era - Norliza Jamaluddin (Tanjong Malim, 2019)
The politeness comments on the Indonesian president Jokowi instagram official account viewed from politico pragmatics and the character education orientation in the disruption era by Norliza Jamaluddin